S3.5a Contamination in sand and water of sea, lakes, and river beaches: Risk factor for fungal human disease. (20th September 2022) - Segal, Esther
Abstract: S3.5 Environmental exposure - risk for human fungal disease, September 21, 2022, 4:45 PM - 6:15 PM Marine and freshwater bodies, such as rivers and lakes are known as possible niches harboring microbes that may affect human health. These ecosystems have been extensively researched, and even regulated, for the presence of bacterial contamination. Fungal contamination has been less researched and lacks regulation, notwithstanding the recent finding that the antifungal resistant yeast species Candida auris has been isolated from a marine ecosystem. The present lecture will focus on a recent collaborative study, involving 13 countries, spanning from the Atlantic to the Eastern Mediterranean coasts, and including the Italian lakes and the Adriatic, Baltic, and Black Seas. The study explored fungal contamination of sand and water of the sea, lakes, and river beaches in 91 bathing sites, and water of 67 of these. This study considered several fungal parameters: all fungi, several species of the genus Aspergillus and Candida, plus other yeasts, allergenic fungi, Dematiaceous fungi, and dermatophytes. The study took in account four variables that might influence the results of the analytical parameters, such as: (1) coast or inland location, (2) urban and non-urban sites, (3) period of the year, and (4) geographical proximity and type of sediment. A site-blind median was found to be 89 Colony-Forming Units (CFU) of fungi per gram of sand in coastal and inland freshwaters, with variability between 0 and 6400 CFU/g. For freshwater sites, that number was 201.7 CFU/g [0, 6400 CFU/g ( P  = .01) and for coastal sites was 76.7 CFU/g (0, 3497.5 CFU/g)]. For coastal waters and all waters, the median was 0 CFU/ml (0, 1592 CFU/ml), and for freshwaters 6.7 (0, 310.0) CFU/ml ( P  <.001). The fungal load in water has to be further corroborated in additional ongoing studies. Some of these will be presented herewith. The lecture will also include, as an example, the data collected at the Israeli Mediterranean coast. This study included a screen of sand and water of six urban beaches, from north to south of the Israeli Mediterranean Coast. Sand samples were extracted by water, and the water wash was cultured and quantitated. Water samples were quantitated as well. The fungi were identified phenotypically, by MALDI-TOF MS system and ITS sequencing. The screen revealed that about 80% of the isolates were molds and about 20% yeasts. The mold species included opportunistic pathogens and potential allergens: Aspergillus fumigatus, Fusarium, Penicillium, and Mucorales species. Yeast isolates included Candida, Cryptococcus and Rhodotorula species. The collaborative study and the example study confirmed the relevance of all variables for some of the fungal parameters. The results suggest that beaches should be monitored for fungi for safer use and better management, and for the benefit of public health.